Epstein-Barr virus encoded latent membrane protein 1 suppresses necroptosis through targeting RIPK1/3 ubiquitination - Liu, Xiaolan (Cell Death Dis, 2018)
Necroptosis is an alternative programmed cell death pathway that is unleashed in the absence of apoptosis and mediated by signaling complexes containing receptor-interating protein kinase 1 (RIPK1) and RIPK3. This form of cell death has recently been implicated in host defense system to eliminate pathogen-infected cells. However, only a few viral species such as herpes simplex virus (HSV) and cytomegalovirus (CMV) have evolved mechanisms inhibiting necroptosis to overcome host antiviral defense, which is important for successful pathogenesis. Here, we show that the γ-herpesvirus Epstein–Barr virus (EBV) blocks necroptosis in EBV-infected human nasopharyngeal epithelial cells and nasopharyngeal carcinoma cells. Our findings indicate that EBV-encoded latent membrane protein 1 (LMP1), which lacks an RIP homotypic interaction motif (RHIM) domain, has mechanisms distinct from RHIM signaling competition to inhibit this necroptotic pathway. Intriguingly, LMP1 interacts directly with both RIPK1 and RIPK3 through its C-terminal activation region. More importantly, LMP1 can modulate the post-translational modification of the two receptor-interacting proteins. We then show that LMP1-mediated promotion of K63-polyubiquitinated RIPK1, suppression of RIPK1 protein expression and inhibition of K63-polyubiquitinated RIPK3 induced a switch in cell fate from necroptotic death to survival. These findings provide direct evidence for the suppression of necroptosis by EBV and define a mechanism of LMP1 to interrupt the initiation process of necroptosis before necrosome formation.